Fixed effects, lagged dependent variables, and bracketing: Cautionary remarks - Matei Demetrescu; Manuel Frondel; Lukas Tomberg; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
We investigate a bracketing property that purports to yield upper- and lower bounds on the treatment effects obtained from a fixed effects- and lagged dependent variable model. Referencing both analytical results and a Monte Carlo simulation, we explore the conditions under which the bracketing property holds, confirming this to be the case when the data generating process (DGP) is characterized by either unobserved heterogeneity or feedback effects from a lagged dependent variable (LDV). However, when the DGP is characterized by both features simultaneously, we find that bracketing of the treatment effect only holds under certain conditions - but not in general. Practitioners can nevertheless obtain the lower bound estimate by referencing a model that includes both fixed effects and a LDV. While the Nickell bias in the coefficient of the LDV is known to be of order 1/T, we show that the Nickell-type bias in the estimator of the treatment effect is of order 1/T squared. – – Wir untersuchen eine Klammereigenschaft, die obere und untere Grenzen für die mit einem Fixed-Effects-Modell und einem Lagged-Dependent-Variable-Modell geschätzten Treatmenteffekte liefern soll. Unter Bezugnahme auf analytische Ergebnisse und eine Monte-Carlo-Simulation untersuchen wir die Bedingungen, unter denen die Klammerungseigenschaft gilt, und bestätigen, dass dies der Fall ist, wenn der datengenerierende Prozess (DGP) entweder durch unbeobachtete Heterogenität oder durch Rückkopplungseffekte von einer verzögerten abhängigen Variable (LDV) gekennzeichnet ist. Wenn der DGP jedoch durch beide Merkmale gleichzeitig charakterisiert ist, stellen wir fest, dass die Klammerung des Treatmenteffekts nur unter bestimmten Bedingungen gilt - aber nicht im Allgemeinen. Anwender können jedoch eine untere Schätzgrenze erhalten, indem sie ein Modell verwenden, das sowohl Fixed-Effects als auch eine LDV enthält. Während die Nickell-Verzerrung im Koeffizienten der LDV bekanntlich die Ordnung 1/T hat, zeigen wir, dass die Nickell-Verzerrung im Schätzer des Behandlungseffekts die Ordnung 1/T zum Quadrat hat.
Keywords: C18; C23; C52; 330; Monte Carlo simulation; treatment effect; bounds; Nickell bias